Narratives of Black Women on Hair in the Workplace - Maria, Sol; Knight, Fernandez; Long, Wahbie (PINS-Psychology in Society, 2019)
Hair is a physical characteristic laden with socio-political significance and, in the case of black women, it remains a complex symbol of racialization, othering and marginalization. In this study, we attempt to present black women’s perspectives on their hair and, by extension, their positions in a historically White institution of higher education. Semi-structured interviews were conducted with fourteen full time staff members in various departments at the University of Cape Town. Key themes from the study revealed how black women used hair as a tool for negotiating and constructing multiple dimensions of their identity, and how–in the midst of institutional conversations about transformation and decolonization–they challenged dominant, ideologically-laden perspectives on hair.